Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1017/jmech.2012.141
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis and Preliminary Evaluation of a Spring-Loaded Upper Limb Exoskeleton for Resistance Training with Overload Prevention

Abstract: Resistance training has been shown to be effective for developing musculoskeletal strength and is recommended by many major health organizations, such as the American College of Sports Medicine and the American Heart Association. This form of training is available for most populations, including adolescents, healthy adults, the elderly, and the clinical population. Resistance training equipment design relies heavily on the analysis of human movement. Dynamic models of human movement help researchers identify k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This article extends the results of our previous static and dynamic studies [18][19]. The fundamental contributions of this article are as follows: (1) well-established and wellplanned experiments were conducted, analyzed, and interpreted; (2) zero-free-length spring design influenced exoskeleton performance as compared with free-weight exercise; (3) the feasibility of a spring-loaded upper-limb resistance training exoskeleton and its underlying design issues were tested.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…This article extends the results of our previous static and dynamic studies [18][19]. The fundamental contributions of this article are as follows: (1) well-established and wellplanned experiments were conducted, analyzed, and interpreted; (2) zero-free-length spring design influenced exoskeleton performance as compared with free-weight exercise; (3) the feasibility of a spring-loaded upper-limb resistance training exoskeleton and its underlying design issues were tested.…”
Section: Introductionmentioning
confidence: 62%
“…We found that link 2 had a larger mass moment of inertia in the current exoskeleton design relative to the 1 kg dumbbell, which agrees with the experimental results described in Figure 8(a-b). Therefore, the mass of the linkage should further conform to certain additional constraints with respect to the mass moment of inertia of the dumbbell and the linkage, which can be obtained from the dynamic analysis [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations